2013
DOI: 10.1099/mic.0.063255-0
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of MDCK cell tight junctions by the free-living amoeba Naegleria fowleri

Abstract: Naegleria fowleri is the aetiological agent of primary amoebic meningoencephalitis. This parasite invades its host by penetrating the olfactory mucosa. However, the mechanism of epithelium penetration is not well understood. In the present study, we evaluated the effect of N. fowleri trophozoites and the non-pathogenic Naegleria gruberi on Madin-Darby canine kidney (MDCK) tight junction proteins, including claudin-1, occludin and ZO-1, as well as on the actin cytoskeleton. Trophozoites from each of the free-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Investigations of the early stages of PAM demonstrated that 1 h after instillation of the amoebae, they interacted with the mucus present in the nasal cavity and that, at 6 h post-inoculation, the trophozoites were surrounded by an acute inflammatory reaction, mainly consisting of neutrophils (Cervantes-Sandoval et al, 2008a); however, this innate response appeared to be insufficient to eliminate N. fowleri. Then, at 12 h post-inoculation, the amoebae attached to and penetrated the olfactory neuroepithelium (Rojas-Hern andez et al, 2004;Cervantes-Sandoval et al, 2008a;Shibayama et al, 2013). Furthermore, at 30 h postinfection, trophozoites were found in the cribriform plate, and at 48-72 h post-infection, amoebae reached the OBs without causing an inflammatory reaction (Jarolim et al, 2000;Rojas-Hern andez et al, 2004).…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations of the early stages of PAM demonstrated that 1 h after instillation of the amoebae, they interacted with the mucus present in the nasal cavity and that, at 6 h post-inoculation, the trophozoites were surrounded by an acute inflammatory reaction, mainly consisting of neutrophils (Cervantes-Sandoval et al, 2008a); however, this innate response appeared to be insufficient to eliminate N. fowleri. Then, at 12 h post-inoculation, the amoebae attached to and penetrated the olfactory neuroepithelium (Rojas-Hern andez et al, 2004;Cervantes-Sandoval et al, 2008a;Shibayama et al, 2013). Furthermore, at 30 h postinfection, trophozoites were found in the cribriform plate, and at 48-72 h post-infection, amoebae reached the OBs without causing an inflammatory reaction (Jarolim et al, 2000;Rojas-Hern andez et al, 2004).…”
Section: Pathogenesismentioning
confidence: 99%
“…When an infection of the protozoan occurs, it can damage tissues after the invasion to the CNS. A broad battery of mechanisms, such as poreforming proteins, proteases and adhesion-mediating glycoproteins, among others, are involved in the pathogenic mechanisms through which N. fowleri acts (Aldape et al, 1994;Herbst et al, 2002;Serrano-Luna et al, 2007;Shibayama et al, 2013) (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Penetration of the olfactory epithelium in mice occurred without cellular disruption or damage (390), and microscopy studies have shown that N. fowleri may be ingested by sustentacular cells within the epithelium or may migrate between the sustentacular cells (393). A recent study demonstrated that N. fowleri degraded the epithelial tight junction proteins claudin-1 and zonula occludens-1 in vitro, highlighting a potential paracellular mechanism of penetration (394).…”
Section: Protozoamentioning
confidence: 99%
“…; Khan and Siddiqui ; Shibayama et al. ). To evaluate the damage produced by the amoebic proteases, we preincubated the trophozoites and their CM with E‐64 or Aprotinin and observed that the cysteine proteases inhibitor but not the serine proteases exerted a protective effect on the endothelial monolayer.…”
Section: Discussionmentioning
confidence: 99%